A Study Of Industrial Wastewater Treatment Methodology Recycling And Reuse - Inbavalli, M; Vignesh, G (International Journal of Computer Sciences and Engineering, 2025)
The water is essential for all living things globalization uses industrialization usage of water global warming is emerging elute of water scarcity one aspect to reduce water scarcity is by water recycling. Reuse the pure water and drinking water. First process of wastewater treatment it is a step by step process. Another step recycling process solid removal oil and grease removal biodegrable organics, trickling processed removal toxic material and reuse for agriculture industrial urban reuse environmental reuse this process is low cost and low processing in the wastewater. This paper cover the a study of industrial wastewater treatment method, recycling and reuse.